The Being of Nothingness - Sevilla Godínez, Héctor (Philosophy & theology, 2017)
The reader will find a proposal of philosophical comprehension of nothingness. The intent of this article is to express in nineteen concrete categories that which can be understood by nothingness in the realm of metaphysics. Among other things: that nothingness is, that there is no manner of directly knowing it, that it contains the world without a will, that it is neither deity nor creator, at the same time that it is un-created, incontingent, atimely, absolute, generator of uncertainty, conditioning, and pre-existing to everything that is; in that sense, nothingness implies movement, is enabling, and is associated to chaos and the cosmos.